1994
DOI: 10.1152/ajpcell.1994.266.1.c165
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory volume decrease in cultured astrocytes. I. Potassium- and chloride-activated permeability

Abstract: Regulatory volume decrease (RVD) in detached cerebellar astrocytes in culture after acute exposure to hyposmolarity was characterized in this and the accompanying paper [H. Pasantes-Morales, R. A. Murray, R. Sanches-Olea, and J. Moran. Am. J. Physiol. 266 (Cell Physiol. 35): C172-C178, 1994]. RVD was independent of extracellular calcium, was accelerated at pH 8-9 and retarded at pH 6, and was reduced at temperatures < 18 degrees C. The cationic pathway activated by hyposmolarity was specific for K+ and Rb+, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
56
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 16 publications
11
56
1
1
Order By: Relevance
“…in Hoffmann et al, 2009). In other cells-such as brain cells-following hypotonic swelling, depolarization generated by the Cl -efflux occurs across the volume-regulated Cl -channel, and in these cells RVD is essentially Ca 21 -independent (Pasantes- Morales et al, 1994;Morán et al, 1997) and the K 1 regulatory fluxes permeate across voltage-gated K 1 channels. Subtypes of Kv involved in the different cell types include Kv1.3 in lymphocytes and murine spermatozoa, Kv1.4.2 and Kv1.4.3 in myocytes, and Kv1.5 in lymphocytes and spermatozoa.…”
Section: The Role Of Channels In Regulatory Volume Decreasementioning
confidence: 99%
“…in Hoffmann et al, 2009). In other cells-such as brain cells-following hypotonic swelling, depolarization generated by the Cl -efflux occurs across the volume-regulated Cl -channel, and in these cells RVD is essentially Ca 21 -independent (Pasantes- Morales et al, 1994;Morán et al, 1997) and the K 1 regulatory fluxes permeate across voltage-gated K 1 channels. Subtypes of Kv involved in the different cell types include Kv1.3 in lymphocytes and murine spermatozoa, Kv1.4.2 and Kv1.4.3 in myocytes, and Kv1.5 in lymphocytes and spermatozoa.…”
Section: The Role Of Channels In Regulatory Volume Decreasementioning
confidence: 99%
“…Pharmacological studies have suggested that astrocyte swelling can also elicit an increase in K + conductance (Pasantes-Morales et al, 1994). However, electrophysiological evidence for K + channel activated by hypotonicity is still lacking.…”
Section: Effect Of Dcpib On Swelling-activated Currents In Rat Primarmentioning
confidence: 99%
“…Indeed, astrocytes in culture swell after exposure to solutions of reduced osmolarity and then recover cell volume despite the persistence of the hyposmotic condition (Kimelberg & O'Connor, 1988;Lewis & Donaldson, 1990). It has been shown that RVD in astrocytes is inhibited by the chloride exchanger blockers 4,4'-diisothiocyanatostilbene-2,2'-disulphonic acid (DIDS), 4-acetamido-4'-isothiocyanatostilbene-2,2'-disulphonic acid (SITS), niflumic acid and anthracene 9-carboxylic acid (9-AC; Kimelberg, Rose, Barron, Waniewski & Cragoe, 1989; Sanches-Olea, Pena, Moran & Pasantes-Morales, 1993;Pasantes-Morales, Murray, Lilja & Moran, 1994). Swelling of astrocytes was shown to cause changes in electrophysiological properties (Kimelberg & O'Connor, 1988;Walz & Mukerji, 1988; Kimmelberg, Anderson & Kettenmann, 1990a).…”
Section: Introductionmentioning
confidence: 99%